Compared effectiveness of sodium zirconium cyclosilicate and calcium polystyrene sulfonate on hyperkalemia in patients with chronic kidney disease - Nakayama, Takashin; Yamaguchi, Shintaro; Hayashi, Kaori; Uchiyama, Kiyotaka; Tajima, Takaya; Azegami, Tatsuhiko; Morimoto, Kohkichi; Yoshida, Tadashi; Yoshino, Jun; Monkawa, Toshiaki; Kanda, Takeshi; Itoh, Hiroshi (Frontiers in Medicine, 2023)
Hyperkalemia is a well-recognized electrolyte abnormality in patients with chronic kidney disease (CKD). Potassium binders are often used to prevent and treat hyperkalemia. However, few studies have evaluated the difference in serum potassium (K+) level-lowering effect during the post-acute phase between the novel potassium binder, sodium zirconium cyclosilicate (ZSC), and conventional agents. This retrospective study included patients who received potassium binders (either ZSC or calcium polystyrene sulfonate [CPS]) in our hospital between May 2020 and July 2022. The patients were divided into the ZSC and CPS groups. After propensity score matching, we compared changes from baseline to the first follow-up point, at least 4 weeks after initiating potassium binders, in electrolytes including K+ level between the two groups. Of the 132 patients, ZSC and CPS were administered in 48 and 84 patients, respectively. After matching, 38 patients were allocated to each group. The ZSC group showed greater reduction in K+ levels than did the CPS group (P < 0.05). Moreover, a significant increase in serum sodium minus chloride levels, a surrogate marker for metabolic acidosis, was observed in the ZSC group (P < 0.05). Our results demonstrated that ZSC could potentially improve hyperkalemia and metabolic acidosis in patients with CKD.